A SEQUENCING PROBLEM IN THE WEAVING INDUSTRY - AlHaboubi, M.H. (2020)
The problem of sequencing jobs on a weaving machine is considered where set-up costs are included. The structure of the set-up cost is utilized to develop a polynomial time solution algorithm. The algorithm involves computing the shortest path of a network. An example is solved.